Orang Sungai penyunting, Rosazman Hussin, Jalihah Md. Shah, Dayu Sansalu - Rosazman Hussin; Jalihah Md. Shah; Dayu Sansalu (Siri etnik Sabah, 2012)
History and traditions of Orang Sungai, groups of communities residing in rural areas along the Kinabatangan River, Paitan, Labuk, and Kudat in Sabah, Malaysia.